Beyond Crystallinity: Using Raman Spectroscopic Methods to Further Define Aggregated/Supramolecular Structure of Cellulose - Agarwal, Umesh P. (Frontiers in Energy Research, 2022)
In the bio-based economy, conversion of biomass to biofuels and other products is essential so 10 that a sustainable alternative to fossil fuels can be developed. For this to become a reality, 11 understanding of the biomass ultrastructure is critically important. For instance, to enhance the 12 yield of fermentable sugars from enzymatic hydrolysis of cellulose, the understanding of the 13 latter’s supramolecular structure as well as the ability to modify it appropriately are essential. 14 Although cellulose crystallinity is one way to define the aggregated structure, past research has 15 shown that merely studying how cellulose crystallinity influences the hydrolysis is not good 16 enough. This deduction is based on the fact that not only most crystallinity estimation methods 17 have limitations, but also, that crystallinity measurement inadequately defines the aggregated 18 state of cellulose. Therefore, better approaches to describe the ultrastructure are needed. Raman 19 spectroscopy is particularly well suited to this task because, in addition to crystallinity, several 20 pieces of structure-related information can be generated that when taken together provide a more 21 comprehensive description of the aggregated state. Additionally, the information derived using 22 Raman spectroscopy is more resolved because it comes from spectral features that represent both 23 the aggregated and the molecular states of cellulose. Few examples will be presented to illustrate 24 this capability.